2005
DOI: 10.1515/bc.2005.132
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic persistence of mouse brain CYP1A1 in chronic heme deficiency

Abstract: Previous work has demonstrated that the function of extrahepatic cytochrome P450 CYP1A1 is dependent on the availability of heme. CYP1A1 is involved in the activation of polyaromatic hydrocarbons. In the present study we used a transgenic mouse model with chronic impairment of heme synthesis -female porphobilinogen deaminase-deficient (PBGD -/-) mice -to investigate the effects of limited heme in untreated and b-naphthoflavone (b-NF)-treated animals on the function of CYP1A1 in brain. The heme content of PBGD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…These brain enzymes are unlikely to contribute to overall drug metabolism, however they may contribute to interindividual variation in drug response through local in situ metabolism (Britto and Wedlund, 1992). Although brain CYPs have been shown to be enzymatically active in vitro, it is not clear that there are sufficient necessary cofactors and coenzymes in close enough proximity for them to be active in vivo, nor whether there is sufficient endogenous heme in the brain for induced brain CYPs to be correctly targeted and inserted into appropriate membranes, and to be functional (Meyer et al, 2002(Meyer et al, , 2005. Here we have shown for the first time that both constitutive and induced CYPs are enzymatically functional in vivo.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These brain enzymes are unlikely to contribute to overall drug metabolism, however they may contribute to interindividual variation in drug response through local in situ metabolism (Britto and Wedlund, 1992). Although brain CYPs have been shown to be enzymatically active in vitro, it is not clear that there are sufficient necessary cofactors and coenzymes in close enough proximity for them to be active in vivo, nor whether there is sufficient endogenous heme in the brain for induced brain CYPs to be correctly targeted and inserted into appropriate membranes, and to be functional (Meyer et al, 2002(Meyer et al, , 2005. Here we have shown for the first time that both constitutive and induced CYPs are enzymatically functional in vivo.…”
Section: Discussionmentioning
confidence: 77%
“…As such, it is not clear that there are sufficient necessary cofactors in close enough proximity for brain CYPs to be active in vivo. In the brain, endogenous heme levels have been shown to be rate limiting toward normal CYP function and appropriate membrane insertion, suggesting that basal and induced brain CYPs are not always functional (Meyer et al, 2002(Meyer et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of heme in mammalian neurobiology, however, extends beyond its functions as a direct constituent of mitochondrial cytochromes to being a prosthetic group in a large number of proteins in oxygen sensing and metabolism, detoxification, control of oxidative damage, growth and differentiation, and production of CO and nitric oxide (Padmanaban et al, 1989;Jover et al, 2000;Meyer et al, 2005). A small proportion of heme forms a regulatory pool that can act in a signaling mode by binding to heme-regulatory motifs in a number of proteins, including BK ion channels (Tang et al, 2003), transcription factors such as NPAS2 (neuronal PAS domain protein 2) and Bach1 (BTB and CNC homology 1) (Ogawa et al, 2001;Dioum et al, 2002), and circadian clock and receptor-associated proteins (Kaasik and Lee, 2004;Ghosh et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…F, expression of CYP4X1 gene in control, heme-deficient neurons continuously treated with SA (2-14 DIV) and neurons treated with SA and heme for 12 days (2-14 DIV) measured by real-time PCR; ␤-actin was used as an endogenous reference gene. at ASPET Journals on May 11, 2018 molpharm.aspetjournals.org persistence of the protein (Meyer et al, 2005), and involvement of heme in transcriptional regulation (Dwarki et al, 1987). Our data did not contradict these suggestions but indicated that more time is required to develop heme deficiency in these functional compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of heme is detrimental to neurons and is a contributory factor in cell aging (Chernova et al, 2006), Alzheimer's disease (Atamna and Frey, 2004), and drug-induced neurotoxicity (Meyer et al, 2005). It also diminishes neuronspecific gene expression, alters cellular signaling, and induces apoptosis (Zhu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%